Factors Influencing the Length of Emergency Intensive Care Unit Stay in Adult Tetanus Patients - Xu J; Wang Y; Huang G; Zhou L; Mo X; Yang N; Wu P; Hu S; She C (International Journal of General Medicine)
Ji Xu,1 Ying Wang,2 Guoqing Huang,1 Liping Zhou,1 Xiaoye Mo,1 Ning Yang,1 Ping Wu,1 Shanshan Hu,1 Changshou She1 1Department of Emergency Medicine, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 2Xiangya Medical Academic Promotion Center, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Changshou She, Department of Emergency Medicine, Xiangya Hospital, Central South University, Xiangya Road 87, Changsha, Hunan, 410008, People’s Republic of China, Tel +86 15116331879, Email scs2021@csu.edu.cnObjective: Tetanus remains a public health problem in developing countries. Patients with severe tetanus require long-term access to emergency medical resources. Here, we identified the risk factors for a prolonged length of stay (LOS) in the emergency intensive care unit (EICU) in adult tetanus patients.Methods: We conducted a retrospective study using data from adult tetanus patients admitted to the EICU in our hospitals. K‒M analysis was used for LOS analysis in the EICU, and the Log rank test was used for comparisons between groups. Cox proportional hazards regression model analyses were used to assess significant factors associated with LOS in the EICU.Results: A total of 81 tetanus patients were included in the study. The patients had an average age of 59.39 ± 10.90 years (SD). The mean LOS was 18.1 days (median, 16.0 days; range, 0.6 days to 50.0 days). From 15 related factors, we identified two independent factors for prolonging the LOS of tetanus patients in the EICU: tracheotomy and mechanical ventilation. The risk of EICU retention in patients with mechanical ventilation was 55.3% greater than that in patients without mechanical ventilation (HR=0.447, 95% CI: 0.227– 0.880, P=0.020); the risk of EICU retention was 86.2% greater in patients with tracheotomy than in those without tracheotomy (HR=0.138, 95% CI: 0.058– 0.328, P< 0.001).Conclusion: Tracheotomy and mechanical ventilation support were associated with increased LOS in the EICU in adult tetanus patients, independent of the tetanus antitoxin dose. Clinicians must focus on spasm control and optimize airway management in tetanus patients in the EICU.Keywords: tetanus, intensive care unit, length of stay, influencing factor, tracheotomy, mechanical ventilation